2020
DOI: 10.1063/5.0019480
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio valence bond theory: A brief history, recent developments, and near future

Abstract: This Perspective presents a survey of several issues in ab initio valence bond (VB) theory with a primary focus on recent advances made by the Xiamen VB group, including a brief review of the earlier history of the ab initio VB methods, in-depth discussion of algorithms for nonorthogonal orbital optimization in the VB self-consistent field method and VB methods incorporating dynamic electron correlation, along with a concise overview of VB methods for complex systems and VB models for chemical bonding and reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 156 publications
0
19
0
Order By: Relevance
“…In the 1970s onwards, Goddard et al [41], Harcourt [89] (p. 50), and the present two authors [22,57] (pp. [94][95][96][97], showed again that VB correctly predicts the ground state of O 2 , not only at the ab initio level but already at a simple qualitative level in terms of β integrals and overlaps between atomic orbitals. Nevertheless, this myth still appears even these days in textbooks and papers, as evidenced by a very recent paper on this issue by Corry and O'Malley who try to dispel this myth [90].…”
Section: The O 2 Myth and Mysterymentioning
confidence: 80%
See 3 more Smart Citations
“…In the 1970s onwards, Goddard et al [41], Harcourt [89] (p. 50), and the present two authors [22,57] (pp. [94][95][96][97], showed again that VB correctly predicts the ground state of O 2 , not only at the ab initio level but already at a simple qualitative level in terms of β integrals and overlaps between atomic orbitals. Nevertheless, this myth still appears even these days in textbooks and papers, as evidenced by a very recent paper on this issue by Corry and O'Malley who try to dispel this myth [90].…”
Section: The O 2 Myth and Mysterymentioning
confidence: 80%
“…As the two present authors showed [22,57] (pp. [94][95][96][97], O 2 avoids the Pauli repulsion and assumes a triplet ground state which is highly stabilized by resonance in its two three-electron bonds. Similar descriptions were given recently by us [91] and by Borden et al [92].…”
Section: The O 2 Myth and Mysterymentioning
confidence: 99%
See 2 more Smart Citations
“…However, it is fair to say that problems like the homolytic bond breaking of electron-pair bonds are more easily dealt with using VB calculations, which remains an important approach in the toolbox of quantum chemical methods [ 99 , 100 , 101 , 102 , 103 , 104 , 126 , 127 ]. The VB and MO methods have been compared and discussed in several papers, which shed further light on the two approaches [ 128 , 129 , 130 , 131 , 132 , 133 , 134 ].…”
mentioning
confidence: 99%